2014
DOI: 10.1039/c3cp54034k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hydroxyacetonitrile (HOCH2CN) and polyoxymethylene (POM)-derivatives in comets from formaldehyde (CH2O) and hydrogen cyanide (HCN) activated by water

Abstract: Studying chemical reactivity is an important way to improve our understanding of the origin of organic matter in astrophysical environments such as molecular clouds, protoplanetary disks, and possibly, as a final destination, in our solar system bodies such as in comets. Laboratory simulations on the reactivity of ice analogs can provide important insights into this complex reactivity. Here, the role of water as a catalytic agent is investigated under the conditions of simulated interstellar and cometary grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
(33 reference statements)
5
31
0
Order By: Relevance
“…The presence of POM in comets is also supported by experimental results (Schutte et al 1993). POM and POM-like polymers can be formed from the heating of interstellar/cometary ice analogues containing H 2 CO, NH 3 , and H 2 O (Schutte et al 1993;Danger et al 2014;Noble et al 2012;Vinogradoff et al 2011). In this contribution we show an additional pathway for POM formation induced by radicals that might explain some observation made by the Ptolemy instrument on board Philae.…”
Section: Astrophysical Significancesupporting
confidence: 63%
See 1 more Smart Citation
“…The presence of POM in comets is also supported by experimental results (Schutte et al 1993). POM and POM-like polymers can be formed from the heating of interstellar/cometary ice analogues containing H 2 CO, NH 3 , and H 2 O (Schutte et al 1993;Danger et al 2014;Noble et al 2012;Vinogradoff et al 2011). In this contribution we show an additional pathway for POM formation induced by radicals that might explain some observation made by the Ptolemy instrument on board Philae.…”
Section: Astrophysical Significancesupporting
confidence: 63%
“…Around 200 K several characteristic ions are observed at m/z 32, 47, 60, and 61 owing to the partial co-desorption of GA and POM (Table 4). More precisely, the desorption of GA is detected at 195 K from the m/z 32 and 60, while the POM desorption is observed at 205 K from its characteristic fragments m/z 47 and 61 (Duvernay et al 2014;Hiraoka et al 2005;Danger et al 2014). The last compound that shows up at 234 K is characterised by two ions at m/z 47 and 61 that could also be due to POM desorption (Table 4).…”
Section: Vuv Photolysis Of Pure H 2 Co Solid Filmmentioning
confidence: 94%
“…The B3LYP relative energies are given for all isomers, while CCSD(T) (bold in parenthesis) relative energies are given only for the three lowest energy isomers. 7 21 a) combined CCSD(T)/anharmonic B3LYP calculation, see equation 1b) anharmonic B3LYP c) in parentheses, results of anharmonic CCSD(T) computations 1 d) two sites were observed with the most intense reported in the table (Fig.1) e) out of detection range f) Relative intensities given with respect to ν 5 located at 1419 cm -1 (experimental) rather than the most intense mode which is outside of our measurement range. g None of the computed overtones has an intensity higher than 1 km mol -1 and are not reported h) lower limit of absolute intensity…”
Section: Figmentioning
confidence: 99%
“…Comets could also contain these compounds since precursors are present and photochemical but also thermal processes to synthesize them in this medium can also be envisaged when approaching the Sun. [7] On the Cyanohydrins are usually formed by addition of hydrogen cyanide to aldehydes or ketones while the elimination of HCN from cyanohydrins is easily observedu pon heating. The low thermals tability of these highly boiling compounds leads to difficult studies in the gas phase where partial or complete decomposition is usually observed.…”
Section: Introductionmentioning
confidence: 99%